Astrocyte Progenitors Derived From Patients With Alzheimer Disease Do Not Impair Stroke Recovery in Mice. Issue 10 (16th September 2022) - Välimäki, Nelli-Noora; Bakreen, Abdulhameed; Häkli, Sara; Dhungana, Hiramani; Keuters, Meike H.; Dunlop, Yannick; Koskuvi, Marja; Keksa-Goldsteine, Velta; Oksanen, Minna; Jäntti, Henna; Lehtonen, Šárka; Malm, Tarja; et al.
Abstract : Background: Species-specific differences in astrocytes and their Alzheimer disease-associated pathology may influence cellular responses to other insults. Herein, human glial chimeric mice were generated to evaluate how Alzheimer disease predisposing genetic background in human astrocytes contributes to behavioral outcome and brain pathology after cortical photothrombotic ischemia. Methods: Neonatal (P0) immunodeficient mice of both sexes were transplanted with induced pluripotent stem cell–derived astrocyte progenitors from Alzheimer disease patients carrying PSEN1 exon 9 deletion (PSEN1 ΔE9), with isogenic controls, with cells from a healthy donor, or with mouse astrocytes or vehicle. After 14 months, a photothrombotic lesion was produced with Rose Bengal in the motor cortex. Behavior was assessed before ischemia and 1 and 4 weeks after the induction of stroke, followed by tissue perfusion for histology. Results: Open field, cylinder, and grid-walking tests showed a persistent locomotor and sensorimotor impairment after ischemia and female mice had larger infarct sizes; yet, these were not affected by astrocytes with PSEN1 ΔE9 background. Staining for human nuclear antigen confirmed that human cells successfully engrafted throughout the mouse brain. However, only a small number of human cells were positive for astrocytic marker GFAP (glial fibrillary acidic protein), mostly located in the corpus callosum and retaining complex human-specific morphology with longer processes compared with host counterparts. While host astrocytes formed the glial scar, human astrocytes were scattered in small numbers close to the lesion boundary. Aβ (beta-amyloid) deposits were not present in PSEN1 ΔE9 astrocyte-transplanted mice. Conclusions: Transplanted human cells survived and distributed widely in the host brain but had no impact on severity of ischemic damage after cortical photothrombosis in chimeric mice. Only a small number of transplanted human astrocytes acquired GFAP-positive glial phenotype or migrated toward the ischemic lesion forming glial scar. PSEN1 ΔE9 astrocytes did not impair behavioral recovery after experimental stroke.